The target of a crime under the Article 330 of the Criminal Code of Ukraine - V. Yu. Boichuk (Law and Safety)
From the standpoint of philosophical ontology the author has determined the notion and nature of information constituting official information gathered in the course of operative and search or counterintelligence operations and in the defense sphere of the country as the target of a crime under the Art. 330 of the Criminal Code of Ukraine. The place of this information has been specified in the list of information types determined by the current legislation of Ukraine.